PERUBAHAN KIMIA DAN MIKROBIOLOGI TEMPE BUSUK SELAMA FERMENTASI - Vivi Nuraini; Irvia Resti Puyanda; Widasari Atrilania Sri Kunciati; Laurensia Atha Margareta (Faculty of Agricultural Technology, University of Jember, 2021)
Tempeh is a very popular food because it is delicious and has good nutritional value. Overfermented tempeh is used as a seasoning in dishes such as lodeh and sambal tumpang. Thus, it is necessary to know the length of time tempeh fermentation is safe for consumption. The purpose of this study was to determine the chemical and microbiological quality of over-fermented tempeh and the effect of the packaging used. This study used a 2-factor factorial completely randomized design. The first factor is the storage time of tempeh (1 day, 3 days, 5 days, 7 days, and 9 days), and the second factor is the type of tempeh packaging (plastic, teak leaves, and banana leaves). The results of the water content test showed that the tempeh began to decay in storage for 5 days. Teak leaf packaging has the lowest water content of the others. Tempeh, which has the highest protein content of 0.60 g/L, is tempeh packaged in teak leaves that has been stored for 3 days. Tempeh stored for 9 days has high water content, exceeding the maximum SNI standard (SNI 3144:2015) by about 65%. Soluble protein levels increased and then decreased during the decomposition process. Free fatty acids continued to experience a decrease in storage for 9 days, which indicated that the process of decay had occurred. The highest free fatty acids were found after 3 days of storage in plastic packaging, which reached 6.2 mg NaOH/g, while tempeh packaged with teak on the third day still showed a lower value of 3.83 mg NaOH/g. The total bacteria test showed an increasing trend from the first day to the ninth day of storage. Tempeh was still suitable for consumption up to five days after being stored. After 5 days of storage, tempeh has decreased in quality. Teak leaves have been proven to be able to maintain the quality of tempeh better than plastic packaging or banana leaf packaging. Keywords: banana leaf, FFA (free fatty acid), teak leaf, tempeh